Urgensi Sistem Pengamanan pada Sertifikat Tanah Digital - Candya Upavata Kutey Karta Negara; Ni Wayan Widya Pratiwi; Prisca Dwi Maylinda (CV Rewang Rencang, 2021)
One of the effects of the covid-19 pandemic has altered the workings of the Indonesian people towards the digital world. This harmonizes with the government's agenda of “Making Indonesia 4.0”. Therein lies the acceleration management of the digital development of national infrastructure. Digital soil certificate manufacturing it's a key to supporting government agendas and addressing issues of conventional land. As for the results obtained from this study, it shows that the Blockchain system provides protection against the digital soil certificate because of its decentralized way of doing it using encryption cryptography and descriptions to validate originality data. Thus, the Blockchain is a solutive measure as a means to tackling the digitized problems of national infrastructure